Assessing Salt Tolerance of Range Species Through Vegetation Monitoring - Mauria, S; Harsh, L N (Annals of Arid Zone, 2016)
Vegetation on saline, sandy clay-loam pocket of a protected ntlural range- land in western Rajasthan was monitored for eight years. Salt tolerance of different species has been interpreted from their occurrence and productivity under different soil salinities.